Evaluation of Phytochemical, Antimicrobial, Antioxidant Activity and Cytotoxic Potentials of Agave americana - Pandey, Binayak Raj; Shrestha, Angela; Sharma, Nisha; Shrestha, Bhupal Govinda (Nepal Journal of Biotechnology, 2019)
Ethnomedicinal plants are being used as a source of medicine from ancient time but they lack the proof of modern scientific evidence for their effectiveness. This study focuses on the evaluation of phytochemical, antimicrobial, antioxidant properties of one of the ethnomedicinal plant Agave americana from Dhulikhel region of Nepal. The plant extract was prepared using solvent-based warm soxhlet extraction from the leaves of the plant and antimicrobial activity against six different non-resistant clinical isolates of bacteria (Staphylococcus aureus, Shigella, Klebsiella pneumoniae, Escherichia coli, Bacillus thuringiensis, and Salmonella paratyphi) was evaluated using agar disc diffusion method along with qualitative analysis for presence/absence of phytochemicals. Antioxidant activity was measured by DPPH assay and the cytotoxicity was evaluated using MCF-7 (human breast adenocarcinoma) cancer cell. Presence of phytochemicals like alkaloids, flavonoids, reducing sugars and saponins were detected in the plant extract. The extract was found to show some level of antimicrobial activity against Staphylococcus aureus, Escherichia coli and Bacillus thuringiensis at 50, 100 and 200 mg/ml. The IC50 value of the extract was found to be 7.68 μg/ml. The extracts of Agave americana showed 50 % cell-death of MCF-7 in 12 h at 5 μg/ml. Although this study provided some scientific evidence for the medicinal value of Agave americana, further studies are still needed for the detailed evaluations of every molecule present in this plant along with screening in larger geographical area of Nepal.